Refined Ordovician timescale reveals no link between asteroid breakup and biodiversification - A. Lindskog (Nature Portfolio, 2017)
The high amount of L-type chondrites discovered in Ordovician sediments has previously been linked with the Great Ordovician Biodiversification Event. But here, Lindskoget al. present new zircon ages that date the chondrite dispersion to 468.0±0.3 Ma, showing that the two events may be unrelated.